IOS APPLICATION FOR FINDING HALAL FOOD, MOSQUE, QIBLA DIRECTION AND PRAYER TIME - Dwi, Febria Roosita (Jurnal Informatika, 2015)
Muslim sometimes has trouble when they travel to a new place for find where the location of the halal food and mosque near their location is. Other things that Muslim will have difficulty when they travel in to a new place are find the Qibla direction, pray time in local time and the mosque location near their location. From that problem MLH (Muslim Little Helper) want to help them to solve their problem. The process is carried out as follows: The app get the user location, send the location to the YELP API server and muslimshalat.com API to get the location of halal food, and mosque (using YELP) and for find the direction of Qibla and the prayer schedule (by using muslimshalat.com API). After the system get the data, then it will show on the Map (using apple map inside the app) and put the data as marker. For the Qibla direction and prayer time, it will show in arrow image and listview. This app will be use Swift for the development language. The test result shows that the YELP API can be use only in USA, and internet play as the main rule in this app, because to create connection to the server to pull the data, the system need internet to pass all the data to server.